Analisa Alokasi Memori dan Kecepatan Kriptograpi Simetris Dalam Enkripsi dan Dekripsi - Resianta Perangin-angin; Indra Kelana Jaya; Benget Rumahorbo; Berlian Juni R Marpaung (Journal Information System Development, 2019)
Currently the focus of cryptography is on the security and speed of data transmission. Cryptography is the study of how to secure information. This security is done by encrypting the information with a special key. This information before being encrypted is called plaintext. After being encrypted with a key called ciphertext. At present, AES (Advanced Encryption Standard) is a cryptographic algorithm that is safe enough to protect confidential data or information. In 2001, AES was used as the latest cryptographic algorithm standard published by NIST (National Institute of Standard and Technology) in lieu of the DES (Data Encryption Standard) algorithm that has expired. The AES algorithm is a cryptographic algorithm that can encrypt and decrypt data with varying key lengths, namely 128 bits, 192 bits, and 256 bits. From the results of tests carried out for speed and classification memory, it can be concluded that the AES cryptographic algorithm is superior or faster if the size or size of the plaint text is not so large, because for the smaller AES algorithm the speed ratio in terms of encryption will become more fast, it becomes very different for the Blowfish algorithm itself where for large sizes plaint text can be encrypted faster than AES but for smaller sizes Blowfish is certainly slower in that case, for memory allocation in this case from the tests performed it can be concluded that AES requires more storage space or larger memory allocation compared to the blowfish algorithm